PERLINDUNGAN HUKUM BAGI PEKERJA MIGRAN PEREMPUAN YANG MENJADI KORBAN PERDAGANGAN ORANG (Studi di Kepolisian Daerah Jawa Timur) - Ristiani . (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Ristiani, Prof. Dr. Rachmad Safa'at, S.H., M.Si., Syahrul Sajidin, S.H., M.H.Faculty of Law, Brawijaya University Jl. MT Haryono No. 169 MalangE-mail: ristywu70@gmail.comAbstract The background of this study explained that there are woman migrant workers who becomevictims of human trafficking did not get appropriate legal protections which regulate in the Law.This research aims to analyze legal protection given by East Java Regional Police and otherrelevant institutions for woman migrant workers who become victims of human trafficking, andto understand what are contributing factors that cause woman migrant workers do not get legalprotection, as well as what are the obstacle factors for relevant stakeholders in order to giveappropriate legal protection for woman migrant workers who become victims of humantrafficking. This study uses sociological juridical methods with legal sociology and criminologyapproaches. Based on the results of this study, the government and other relevant institutionshave not given optimal legal protection based on Law Number 21 of 2007 concerning theEradication of the Criminal Act of Trafficking in Persons and Law Number 18 of 2017 concerningthe Protection of Indonesian Migrant Workers towards women migrant workers who becomevictims of human trafficking. Therefore, it needs synergistic cooperation among relatedinstitutions in order to realize adequate legal protection for woman migrant workers who becomevictims of human trafficking.Keyword: Legal protection, workers, woman migrant workers, victims, human traffickingAbstrak Latar belakang dari penelitian ini adalah masih adanya pekerja migran perempuan yang menjadikorban perdagangan orang belum memperoleh perlindungan hukum sebagaimana mestinya yangada dalam undang-undang. Penelitian ini bertujuan untuk menganalisis perlindungan hukum yangdiberikan oleh Kepolisian Daerah Jawa Timur dan pihak-pihak lain yang berkaitan kepada pekerjamigran perempuan yang menjadi korban perdagangan orang serta mengetahui faktor apa sajayang menyebabkan pekerja migran perempuan belum memperoleh perlindungan hukum sertafaktor penghambat para pihak-pihak terkait dalam memberikan perlindungan hukumsebagaimana mestinya kepada pekerja migran yang menjadi korban perdagangan orang.Penelitian ini menggunakan metode yuridis sosiologis dengan pendekatan sosiologi hukum danpendekatan kriminologi hukum. Dari hasil penelitian ini, pemerintah serta para pihak-pihak terkaityang berwenang memberikan perlindungan hukum belum optimal dalam memberikanperlindungan hukum berdasarkan Undang-Undang Nomor 21 Tahun 2007 TentangPemberantasan Tindak Pidana Perdagangan Orang dan juga Undang-Undang Nomor 18 Tahun2017 Tentang Pelindungan Pekerja Migran Indonesia kepada pekerjaan perempuan yang menjadikorban perdagangan orang sehingga dibutuhkan kerjasama yang bersinergi antara lembaga satu dengan lainnya agar terwujud perlindungan hukum yang memadai bagi pekerja migran perempuan yang menjadi korban perdagangan orang.Keyword: Perlindungan hukum, pekerja, pekerja migran perempuan, korban,perdagangan orang.